Comparison of Average Abnormal Return and Average Trading Volume Activity Among LQ45 Companies Before and After the 2024 Indonesia Presidential Election - Ari Kurnianto; Prastiwi, Arum (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This study examines the impact of the 2024 Indonesian Presidential Election on the Indonesian capital market through an analysis of Average Abnormal Return (AAR) and Average Trading Volume Activity (ATVA) on LQ45 index stocks. Using the event study method, this study compares the periods before and after the presidential election to identify changes in market behavior. Statistical testing results indicate no significant differences in AAR and ATVA during the observation period, suggesting that investors do not view the presidential election as an event influencing investment decisions. This finding confirms the efficient market theory, where political information is fully reflected in stock prices. However, sectoral analysis reveals heterogeneous responses, with the healthcare and basic materials sectors showing distinct patterns. The contribution of this research is to provide empirical evidence of the efficiency of the Indonesian capital market and to identify variations in sectoral responses to political events.